Finger Lime: An Alternative Crop with Great Potential in South Florida - Aditya Singh; Edward A. Evans; Jeff Wasielewski; Manjul Dutt; Jude Grosser (EDIS)
Cylindrical Australian finger limes (Microcitrus australasica) taste like a combination of lemon, lime, and grapefruit, come in a rainbow of colors, and have a texture like caviar. Like other citrus fruits, finger limes are nutritious, low in calories, and vitamin-rich. So far in the United States only California grows finger limes commercially, but this 4-page fact sheet written by Aditya Singh, Edward Evans, Jeff Wasielewski, Manjul Dutt, and Jude Grosser and published by the UF/IFAS Food and Resource Economics Department makes the case that exotic, colorful finger limes would likely grow well in Florida, where they would appeal to hoteliers and restaurants and to adventurous, health-conscious consumers on the lookout for a delicious new fresh fruit snack to try. http://edis.ifas.ufl.edu/fe1033